DOI: 10.31979/etd.jngv-yu34
|View full text |Cite
|
Sign up to set email alerts
|

Amount of International News by Four World Newspapers

Abstract: The Toronto Star, have the power to enlighten countries and shape public opinion domestically and abroad. However, at times, newspapers tend to be biased and reflect ideologies or values, which tend to be slanted towards home cultures and personal politics. Consequently, the public often suffers because what it learns about the world may be distorted. As a result, newspapers have witnessed a steady decline in readership following the end of the Cold-War and continuing throughout post-9/11. Irrespectively, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…While some HEIs in the United States reported significant increases in the number of applications, this will not translate necessarily in actual enrolments, because the same student may be simply applying to a larger number of institutions, or may apply, be admitted, but later unable to obtain a visa or travel to the United States. Additionally, reports show that international students tend to adopt a cautious “hedge their bet” approach, given the complexity and uncertainty in the pandemic, by applying to more than one country (Mitchell, 2021 ). It is also noteworthy that the sample used by Martell and Baer ( 2021 ), while impressive and representative of HEIs that attract significant numbers of international students, included only 16% of respondents from associate's‐level institutions or community colleges, while this is the sector most affected by the declines.…”
Section: A Comparative Analysis Of Enrolment Trends Post‐covidmentioning
confidence: 99%
“…While some HEIs in the United States reported significant increases in the number of applications, this will not translate necessarily in actual enrolments, because the same student may be simply applying to a larger number of institutions, or may apply, be admitted, but later unable to obtain a visa or travel to the United States. Additionally, reports show that international students tend to adopt a cautious “hedge their bet” approach, given the complexity and uncertainty in the pandemic, by applying to more than one country (Mitchell, 2021 ). It is also noteworthy that the sample used by Martell and Baer ( 2021 ), while impressive and representative of HEIs that attract significant numbers of international students, included only 16% of respondents from associate's‐level institutions or community colleges, while this is the sector most affected by the declines.…”
Section: A Comparative Analysis Of Enrolment Trends Post‐covidmentioning
confidence: 99%
“…In Europe, where longitudinal data are most readily available, the number of English-taught programmes more than trebled in the seven years from 2007 (2,389 programmes) to 2014 (8,089 programmes) (Wächter and Maiworm 2014), with the number likely to be even higher today. Beyond Europe, a recent study identified 27,874 full masters and bachelor degree programmes taught in English at universities in the world's non-English dominant nation states (Mitchell 2021). This ongoing drive to English as a Medium of Instruction (EMI) has generated heated debates across the world, prompting concerns about inequity, injustice and disadvantage at a societal, educational, professional and individual level (De Costa et al 2021;Dimova et al 2015;Shohamy 2012).…”
Section: Introductionmentioning
confidence: 99%